THE EFFECT OF CARRAGEENAN FLOUR ADDITION ON THE PREFERENCE LEVEL OF RED TILAPIA (Oreochromis niloticus) ROLADE - Danella, Amanda Puspa; Junianto, Junianto; Maulina, Ine; Rostini, Iis (Universitas Mataram, 2025)
Fishery product diversification refers to the variety of processed fishery products. One of the fishery commodities that can be used as a raw material for diversification products is red tilapia. Red tilapia meat can be used as a raw material for making roulade. This research aims to determine the optimal percentage of carrageenan flour addition in the production of red tilapia fish rolls to yield the most preferred product by panelists. The study was conducted at the Fishery Product Processing Laboratory of Building 2, Faculty of Fisheries and Marine Sciences, Padjadjaran University. The research method employed was experimental, with four treatments of carrageenan flour addition: 0%, 0.75%, 1%, and 1.25%. The observed parameters were the preference levels for red tilapia fish rolls from all treatments, consisting of appearance, aroma, taste, and texture preferences. Preference level observations were conducted through assessments by 20 semi-trained panelists. Research results indicate that the 1% carrageenan flour addition was most preferred by panelists, with average preference scores for appearance (6.5), aroma (6.6), taste (7.1), and texture (7.6).